2016
DOI: 10.1051/0004-6361/201527898
|View full text |Cite
|
Sign up to set email alerts
|

Transmission spectroscopy of HAT-P-32b with the LBT: confirmation of clouds/hazes in the planetary atmosphere

Abstract: Aims. Spectroscopic observations of a transit event of an extrasolar planet offer the opportunity to study the composition of the planetary atmosphere. This can be done with comparably little telescope time using a low-resolution multi-object spectrograph at a large aperture telescope. We observed a transit of the inflated hot Jupiter HAT-P-32b with the Multi-Object Double Spectrograph at the Large Binocular Telescope to characterize its atmosphere from 3300 to 10 000 Å. Methods. A time series of target and re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(93 citation statements)
references
References 62 publications
(121 reference statements)
6
85
2
Order By: Relevance
“…Previous ground-based observations of the transit of HAT-P-32b in the optical wavelengths (Gibson et al 2013;Zhao et al 2014;Mallonn & Strassmeier 2016;Nortmann et al 2016) did not find evidence of spectral modulations due to molecules. Our cloud top pressure is consistent with their measurements within 1σ, hence the water detection in the infrared is not controversial.…”
Section: Comparison With Other Observationsmentioning
confidence: 65%
See 1 more Smart Citation
“…Previous ground-based observations of the transit of HAT-P-32b in the optical wavelengths (Gibson et al 2013;Zhao et al 2014;Mallonn & Strassmeier 2016;Nortmann et al 2016) did not find evidence of spectral modulations due to molecules. Our cloud top pressure is consistent with their measurements within 1σ, hence the water detection in the infrared is not controversial.…”
Section: Comparison With Other Observationsmentioning
confidence: 65%
“…HAT-P-32b is one of the most inflated exoplanets discovered, being less massive than Jupiter (M M 0.79 p J u p = ) but having almost twice its radius (R R 1.789 p J u p = ). The atmosphere of HAT-P-32b has been observed with ground-based instruments in the optical wavelengths, revealing a featureless transmission spectrum (Gibson et al 2013;Zhao et al 2014;Mallonn & Strassmeier 2016;Nortmann et al 2016). In addition, Zhao et al (2014) suggested the presence of a thermal inversion in the atmosphere of HAT-P-32bto interpret eclipse observations.…”
Section: Introductionmentioning
confidence: 99%
“…We monitored the host star to deduce an upper limit on the star spot coverage and their effect on the transmission spectrum from its photometric variability. Similar photometric monitoring campaigns for different targets are presented, for example, in Mallonn et al (2015b) and Mallonn & Strassmeier (2016). The Lomb-Scargle periodograms in Fig.…”
Section: Stellar Activitymentioning
confidence: 92%
“…Sing et al 2012;Lendl et al 2016;Mallonn & Strassmeier 2016) or highresolution spectroscopy (e.g. Snellen et al 2008;Wood et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of these clouds and hazes is typically shown by a flattening of spectral features in transmission spectra, resulting from the inability of stellar photons to reach depths in the atmosphere below the cloud and haze layers (Gibson et al 2012(Gibson et al , 2013Deming et al 2013;Jordán et al 2013;Mandell et al 2013;Sing et al 2013;Chen et al 2014;Fukui et al 2014;Schlawin et al 2014;Wilkins et al 2014;Mallonn & Strassmeier 2016). Such flat transmission spectra have been seen across many exoplanets of different sizes, effective temperatures, and stellar irradiation levels (e.g., Crossfield et al 2013;Knutson et al 2014aKnutson et al , 2014bKreidberg et al 2014;Sing et al 2016), suggesting that the processes governing cloud and haze formation in exoplanet atmospheres are as complex as they are ubiquitous.…”
Section: Introductionmentioning
confidence: 99%